2008
DOI: 10.2197/ipsjjip.16.93
|View full text |Cite
|
Sign up to set email alerts
|

A Stream-mining Oriented User Identification Algorithm Based on a Day Scale Click Regularity Assumption in Mobile Clickstreams

Abstract: The mobile Internet is characterized by "Easy-come and easy-go" characteristics, which causes challenges for many content providers. The 24-hour clickstream provides a rich opportunity to understand user's behaviors. It also raises the challenge of having to cope with a large amount of log data. The author proposes a stream-mining oriented algorithm for user regularity classification. In the case study section, the author shows the case studies in commercial mobile web sites and presents that the recall rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Church performed sessions and queries analysis of mobile Internet search with large real-world data 6) . The author conducted the regularity study on the mobile clickstreams and reported 80% accuracy in users that revisited the following month using statistical data on regularity 7) The author also did 80% true positive ratio for regularity in long-term mobile web access 8) . His research covered only day-scale behavior.…”
Section: Related Workmentioning
confidence: 99%
“…Church performed sessions and queries analysis of mobile Internet search with large real-world data 6) . The author conducted the regularity study on the mobile clickstreams and reported 80% accuracy in users that revisited the following month using statistical data on regularity 7) The author also did 80% true positive ratio for regularity in long-term mobile web access 8) . His research covered only day-scale behavior.…”
Section: Related Workmentioning
confidence: 99%
“…Church has performed sessions and queries analysis of mobile Internet searching with large real-world data [1]. The author conducted a regularity study on the mobile clickstream and reported 80 % accuracy in users that revisited the following month using statistical data on regularity [6] It showed an 80 % true positive ratio for regularity in long-term mobile web access [8]. However, this research covered only day-scale behavior.…”
Section: Related Workmentioning
confidence: 99%